Habitat and food habits of the endemic fish Oryzias eversi in Tana Toraja, South Sulawesi, Indonesia - TRISKA LAMBA; AMBENG AMBENG; IRMA ANDRIANI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Lamba T, Ambeng, Andriani I. 2023. Habitat and food habits of the endemic fish Oryzias eversi in Tana Toraja, South Sulawesi, Indonesia. Biodiversitas 24: 5137-5145. The population of the medaka fish species, Oryzias eversi, was categorized as Near Threatened by the International Union for Conservation of Nature (IUCN) 2019 due to its restricted distribution and occurrence in a single threatened location. One way to protect this species from extinction is through captive breeding, which requires understanding its habitat conditions and food habits. Therefore, this research aimed to analyze the habitat conditions and food habits of Oryzias eversi (Hadiaty & Nolte, 2012) in Tilanga Pool, Tana Toraja. Purposive random sampling was used to obtain fish samples, while habitat conditions were determined by measuring environmental parameters, and the abundance and diversity of plankton. Food habits were analyzed by calculating the Index of Preponderance (IP) and Relative Gut Length (RGL). The results indicated that O. eversi inhabited a highly polluted habitat with dissolved oxygen content that ranged from 3.95 to 4.16 mg/L. The abundance of phytoplankton and zooplankton ranged from 185-435 cells/L and 10-25 ind/L, respectively. Phytoplankton diversity was in the moderate category, while zooplankton was low, with average values of Diversity Index (H’) ranging from 1.61-1.93 and 0.69-024, respectively. IP and RGL showed that O. eversi was an omnivore-carnivore fish. The average IP of zooplankton and phytoplankton ranged from 0.35-61.11% and 0.69-1.04%, respectively. Meanwhile, the RGL ranged from 0.48 to 0.62, respectively. Cyclops sp. larvae were identified as the primary food source for O. eversi with IP above 40% and Eurycercus sp. with IP range of 4-40% as additional food.